BENDING OF GRAPHENE VIA ELECTROSTATIC ACTUATION - K. Edaan Al-mashaal, Asaad (Antis-Publisher, 2024)
Objective: To explore the potential of graphene in electrostatic actuation, emphasizing its mechanisms, applications, and challenges, and to evaluate its integration with MEMS/NEMS technologies. Method: A detailed literature review was conducted, analyzing the principles of electrostatic actuation and graphene's unique properties. The study examined synthesis and fabrication methods, focusing on scalability, quality control, and defect minimization. Performance metrics such as actuation efficiency, mechanical strain, and response time were also evaluated using data from prior experimental and theoretical studies. Results: Graphene’s exceptional electrical, mechanical, and thermal properties make it a promising material for electrostatic actuators. It demonstrates significant potential in MEMS/NEMS devices, flexible electronics, and biomedical applications. However, challenges persist in achieving consistent large-scale production, minimizing defects, and improving actuation efficiency. The review identifies key strategies for enhancing scalability and stability while maintaining graphene's functional properties. Novelty: This study provides a comprehensive review of graphene-based electrostatic actuators, integrating insights into their mechanisms, synthesis, fabrication challenges, and application prospects. It highlights innovative strategies to overcome existing limitations, offering a roadmap for advancing the practical implementation of graphene in actuator technologies.